Comparison of melanoma guidelines in the U.S.A., Canada, Europe, Australia and New Zealand: a critical appraisal and comprehensive review. (1st January 2014) - Fong, Z.V.; Tanabe, K.K.
Summary: There are several well‐established guidelines for the staging of melanoma and the size of excisional margins, along with recommendations for sentinel lymph node biopsy. Guidelines have been proposed in the U.S.A. (National Comprehensive Cancer Network), Canada (Cancer Care Ontario and Canadian Medical Association), Europe (European Society for Medical Oncology) and Australia and New Zealand (Australian Cancer Network). The guidelines set by these groups are largely based on current evidence, or expert panel consensus where evidence is lacking. The recommendations are more controversial and varying where there is a lack of level‐one evidence in the literature (e.g. screening, adjuvant therapy, follow‐up intensity). We review the evidence and available literature for the management of melanoma worldwide.